Development of method for determining parameters of regulator for controlling the astatic object of third order - Свістельник, Сергій Сергійович; Ткачук, Андрій Геннадійович; Ільницький, Тарас Петрович; Правденко, Руслан Вадимович (Technology audit and production reserves, 2015)
The process of designing the automatic control systems is considered and its main stages are analyzed. The basic laws of regulation and regulators, developed on their basis, are characterized. Types of automatic tuning of regulators consist in three fundamentally important stages: identifying the control object, calculation regulator parameters, more accurate tuning of regulator. Existing methods of regulator choice are considered. It is proposed a new calculation method of regulator parameters to control by astatic object of the third order with astaticism equal to one. The analysis of the qualitative characteristics of the obtaining system is conducted. It is shown that the quality control process is provided using proportional differential control law. It is shown that the calculated parameters of proportional differential regulator provide almost smooth change of initial coordinates of control object, indicating the feasibility of using the proposed method.